If z = f ( x , y ) {\displaystyle z=f(x,y)} , then the first partial derivatives of with respect to x {\displaystyle x} and y {\displaystyle y} are the functions ∂ z ∂ x {\displaystyle {\frac {\partial z}{\partial x}}} and ∂ z ∂ x {\displaystyle {\frac {\partial z}{\partial x}}} , defined as shown. ∂ z ∂ x = lim δ x → 0 f ( x + δ x , y ) − f ( x , y ) δ x {\displaystyle {\frac {\partial z}{\partial x}}=\lim _{\delta x\to 0}{\frac {f(x+\delta x,y)-f(x,y)}{\delta x}}} ∂ z ∂ y = lim δ y → 0 f ( x , y + δ y ) − f ( x , y ) δ y {\displaystyle {\frac {\partial z}{\partial y}}=\lim _{\delta y\to 0}{\frac {f(x,y+\delta y)-f(x,y)}{\delta y}}}
Return to Topics Page
This page were made by Tri Phan